2012
DOI: 10.1080/01639625.2012.726168
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Deviance and Deviants in the Durable Medical Equipment (DME) Field: Characteristics, Consequences, and Responses to Fraud

Abstract: The literature indicates Medicaid fraud is pervasive and comprises a substantial portion of health care spending. One type of Medicaid fraud that has not been explored is durable medical equipment fraud. This study seeks to fill this gap in the literature by examining the characteristics of durable medical equipment fraud cases investigated by Medicaid Fraud Control Units. Content analysis was used to review 258 reported cases of durable medical equipment fraud. The findings indicate that providers engage in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Our study shows that when nurses suffered, particularly because of negative interpersonal relationships with colleagues, line managers or patients, their performance decreased in terms of quality, and deviant behaviours were carried out, reducing the quality of perceived care. This is in line with previous literature showing that conflicts with head nurses or managers (Policastro & Payne, 2013), the perception of injustice within organizations (Ahmed, Kiyani, & Hashmi, 2013;Ceylan & Sulu, 2011), poor leadership styles (Alilyyani et al, 2018;Egues & Leinung, 2013) and lack of social support (Longo & Sherman, 2007) are antecedent to counterproductive work behaviours (Zaghini et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Our study shows that when nurses suffered, particularly because of negative interpersonal relationships with colleagues, line managers or patients, their performance decreased in terms of quality, and deviant behaviours were carried out, reducing the quality of perceived care. This is in line with previous literature showing that conflicts with head nurses or managers (Policastro & Payne, 2013), the perception of injustice within organizations (Ahmed, Kiyani, & Hashmi, 2013;Ceylan & Sulu, 2011), poor leadership styles (Alilyyani et al, 2018;Egues & Leinung, 2013) and lack of social support (Longo & Sherman, 2007) are antecedent to counterproductive work behaviours (Zaghini et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Some specific negative emotions (e.g., hostility) did contribute to the prediction of CWB The purposes of this study were to explore how the supervisor feedback environment influences employee deviance and to examine the mediating role played by work-related stress Participants in this research were 276 registered hospital nurses and 276 supervisors who were asked to complete a cross-sectional questionnaire survey CWB are negatively correlated with constant feedback from supervisors CWB are a partial mediator of the relationship between the environment and the negative emotions experienced by nurses 11 Policastro et al USA, 2013 [31] The aim of this study was to examine the characteristics of medical equipment fraud cases A qualitative study was performed to review 258 reported cases of durable medical equipment fraud.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 14 selected papers, four were qualitative [29][30][31][32] and nine quantitative [8,[33][34][35][36][37][38][39][40]. One of the studies used a mixed-method [41].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations